ANALISIS SEMIOTIK PADA PUISI PERJALANAN KE LANGIT KARYA KUNTOWIJOYO - Neneng Rani Setiani; Rismawati Rismawati; Agus Priyanto (IKIP Siliwangi, 2019)
The background of this research is to help literature lovers to enjoy one of the literary works, namely poetry so that researchers try to find ways to study poetry travel to the sky easily and can understand the meaning implied in the poem. The statement is based on observations from students who have read the poem. This study aims to appreciate the meaning of poetry Travel to Heaven with a study that can be used that is using a semiotic analysis approach. The results of the analysis that the meaning of poetry Travel to Heaven, in general, is the presence of tools and the path to God, for those who really miss God. This must be used before time stops and even freezes.